2018
DOI: 10.1001/jamaophthalmol.2018.0797
|View full text |Cite|
|
Sign up to set email alerts
|

Economic Evaluation of Low-Vision Rehabilitation for Veterans With Macular Diseases in the US Department of Veterans Affairs

Abstract: ; for the LOVIT II Study Group IMPORTANCE Examining costs and consequences of different low-vision (LV) programs provides important information about resources needed to expand treatment options efficiently. OBJECTIVE To examine the costs and consequences of LV rehabilitation or basic LV services. DESIGN, SETTING, AND PARTICIPANTS The US Department of Veterans Affairs (VA) Low Vision Intervention Trial (LOVIT) II was conducted from September 27, 2010, to July 31, 2014, at 9 VA facilities and included 323 veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Depending on agreements between organizations or policies in different countries, low vision rehabilitation services may be provided by commercial, non-profit, or charity organizations. [ 68 ]…”
Section: Discussionmentioning
confidence: 99%
“…Depending on agreements between organizations or policies in different countries, low vision rehabilitation services may be provided by commercial, non-profit, or charity organizations. [ 68 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that vision impairment in Portugal is a common condition that leads to significant costs at personal and societal levels . The general lack of cost‐effectiveness analysis (CEA) may delay decisions to implement more and better basic‐VRS and creates barriers to the development of vision rehabilitation . But, why do we need to perform a CEA now if magnifiers have been dispensed in many hospitals regularly since, at least, 1970? Recent systematic reviews showed that better evidence on the cost‐effectiveness of using magnifiers is necessary .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of knowledge regarding what impact VR can have on those economic issues. 14,19,[29][30][31] Cost-effectiveness analysis (CEA) and health economic analysis will reveal the impact of VR.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there is still lack of studies examining the actual benefits of VR for people with VI. This lack of evidence entails barriers to the development of vision rehabilitation systems (VRS) [31][32][33][34]. Magnifiers, for example, have been dispensed in many hospitals regularly since, at least, 1970 [35].…”
Section: Introductionmentioning
confidence: 99%